(untitled) (Research Nepal Journal of Development Studies, 2020)
Human trafficking is one of the major crimes in the world after trafficking in arms and drugs and one of the fastest growing criminal enterprises because it holds relatively low risk with high profit potential. Causes that contribute to human trafficking are commonly believed to be related to poverty, globalization and economic disparities among countries. Human trafficking is the modern equivalent to slavery. It presents a dangerous threat to the human rights and human dignity of many people each year. To understand Human Trafficking and Modern Day Slavery. To understand how different conflict between SAARC Countries which fuels Human Trafficking, the study has been designed. It is a qualitative descriptive analysis of secondary information. It is simply a literature review of status of human trafficking as modern day slavery in South Asia.